The role of karang taruna youth in improving the economy In kerinci regency - Faisal Amri (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine : To determine and understand the role of Karang Taruna in the development of rural communities, To determine the strength and rules of Karang Taruna in youth empowerment, To determine and understand the function of Karang Taruna as a supporter of the welfare of rural. The Research Approach used in this study : Conceptual Approach, Statute Approach, Historis Approach and Case Approach. The location on this research in Lempur Mudik Village in Gunung Raya District Kerinci Regency. The type of research is normative juridical by studying various literature and legislation, as well as legal theories regarding the role and function of Karang Taruna in Lempur Mudik Village. The results of the study : Karang Taruna is a social community organization as a forum and means of developing every member of the community who grows and develops on the basis of awareness and social responsibility from, by and for the community, especially the younger generation in the village kelurahan area especially engaged in welfare. The growth and development of every qualified, skilled and intelligent member of society is innovative in overcoming social welfare problems, especially the younger generation. The role of Karang Taruna in Lempur Mudik Village has been running well but has not run optimally, this is due to various indicators, especially in making decisions, vision and mission of Karang Taruna